Attributes affecting students’ ability in thinking skills - Hamidah Maidinsah,; Farah Nabillah Mohamed Jizad,; Maslizah Ab Wahab,; Balkish Osman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The Ministry of Education has reemphasized the implementation of higher order thinking skills (HOTS) in science and mathematics curriculum in 2014. In relation to this, a research was carried out to analyse students’ ability in thinking skills (ATS), and to construct a model that estimates their ATS. The study involved 300 students of engineering and science foundation programme from a university. A Scientific Reasoning Test was used as instrument. Binary logistic regression is used to categorize the students’ level of thinking skills. Results show that 51.7% of students are categorized as having higher order thinking skills (HOTS) and 48.3% having lower order thinking skill (LOTS). More male students at HOTS level (57.1%) compared to LOTS (42.9%), while more female students at LOTS level (52.7%) compared to HOTS (47.3%). Higher percentage of boarding school students (55.4%) at HOTS level compared to daily school students. There is a significant correlation between ATS with students’ performance in mathematics course in foundation programme (MAT093) and performance in mathematics subject in SPM (MAT). A binary logistic model was constructed to estimate students’ ATS. The findings implicate that teaching method through inquiry and mind-mapping in i-Think process which has been implemented in schools since 2015 seems to give an impact in enhancing and developing students’ thinking skills.